Peningkatan Kemampuan Berpikir Kritis Matematis Siswa Melalui Penggunaan Metode Improve Pada Materi Sistem Persamaan Linear Dua Variabel - Hawa Liberna (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2012)
This study aimed to analyze the improvement of critical thinking skills Improve mathematical methods to the material system of linear equations of two variables. The method used is the method of quasi-experimental data analysis using different test or the average of the t-test. Population affordable in this study were all students of class VIII A and VIII B grade SMP 248. Samples were obtained through random sampling techniques, namely random sample collection techniques. Testing requirements analysis consists of data from test to test methods Liliefors normality and homogeneity tests to test methods bartlett. Based on the results of the testing requirements of data analysis concluded that the two sets of data were normally distributed and homogeneous. Instrument variable mathematical critical thinking skills is a written test consisting of 20 items about. Based on the results of hypothesis testing and data analysis it can be concluded that the critical thinking skills of students who are taught mathematical improve method is higher than conventional methods. Based on these results, it is in an effort to improve students' critical thinking skills teachers should use mathematical methods improve.